Intravesical Loss of OnabotulinumtoxinA During Endoscopic Intradetrusor Injection - A Multicenter Experience - Šámal, Vladimír; Krhut, Jan; Paldus, Vít; Műllerová, Jana; Mečl, Jan (International neurourology journal, 2020)
PURPOSE: To evaluate intravesical loss of onabolunumtoxinA (onaBTA) during endoscopic injection into the bladder wall for treatment of neurogenic detrusor overactivity (NDO). The intraluminal loss of onaBTA cannot be determined directly, therefore we added methylene blue (MB) to reconstitute onaBTA. Subsequently we used spectrophotometry to determine the total amount of MB in the irrigation fluid, which allowed us to calculate total intraluminal loss of onaBTA. METHODS: The study population was consisted of 48 patients with NDO. The mean age was 36.6±8.9 years. Forty-two patients suffered from NDO due to spinal cord injury and 6 patients suffered from multiple sclerosis. Each patient received 200 units of onaBTA administered by 30 endoscopic injections (1 mL per injection) using a 23-G needle. The entire volume of irrigation fluid was collected and spectrophotometry was used to determine the MB concentration. The total amount of injected onaBTA, total amount of irrigation solution and the known amount of MB used during reconstitution, allowed for the determination of intravesical loss of onaBTA. RESULTS: Forty-five patients were included in the final analysis. The mean volume of irrigation fluid was 603.33±400.14 mL. The mean absorbance was 0.14±0.12 with the mean MB concentration 0.19±0.18 mg/L. The mean calculated loss of onaBTA was 4.14±4.11 units. CONCLUSION: The endoscopic injection of onaBTA marked by MB into the bladder wall is associated with minimal intravesical loss of the agent, representing less than 3% of the administered dose of MB. This may reflect the amount of the onaBTA detected in the irrigation fluid.
Keywords: Urinary bladder, Neurogenic; Methylene blue; Spectrophotometry; Botulinum toxins, Type A; Intravesical injection